VISITORS’ PERCEPTION OF CIREBON AS A TOURIST DESTINATION-BUILDING TO PROMOTE THE CITY - Wendy Purnama Tarigan; Tuti Handayani (ETIKONOMI, 2012)
The problem identified in this study is how visitors’ perception and the image communication influenced the overall image of Cirebon as a tourist destination. This study was conducted by using structural equation modelling. The results of this study show that perception variable equation significantly affected the overall image variable, while the image communication variable did not significantly affect the overall image. On the other hand, the causal relationship equation shows that there is a significant relationship between the exogenous latent variable of perception and endogenous latent variable of Overall Image. While there is no relationship between exogenous latent variable of image Communication with endogenous variable of overall image. The result is expected to give recommendation to the local government to develop and promote tourism that at the end can put tourism to generate income for the city.DOI: 10.15408/etk.v11i1.1872